Respuesta :

Answer:

f(1) = - 1

f(-1) = - 2

Step-by-step explanation:

f(1) will lie in the function f(x) = - 2x + 1

Therefore,

f(x) = - 2x + 1

Plug x = 1

f(1) = - 2*1 + 1 = - 2 + 1 = - 1

f(-1) will lie in the function f(x) = - x - 1

Therefore,

f(x) = - x - 1

Plug x = - 1

f(-1) = - 1 - 1 = - 2

Answer:

  • -1, 0, 1, 11, 3

Step-by-step explanation:

Function 1

  • f(x) = -2x + 1
  • f(1) = -2(1) + 1 = -2 + 1 = -1

Function 2

  • f(x) = -x - 1
  • f(-1) = -(-1) - 1 = 1 - 1 = 0

Function 3

  • f(x) = x + 3
  • f(-2) = -2 + 3 = 1

Function 4

  • f(x) = 2x + 1
  • f(5) = 2(5) + 1 = 11

Function 5

  • f(x) = 3
  • f(6) = 3